KOMPAS BBM (Komunitas Pemuda Desa Bangun Bisnis Mix Farming) Sebagai Sarana Membangun Wirausaha Ternak Bersistem Mix Farming Guna Pemberdayaan Pemuda Desa Pagung Kecamatan Semen Kabupaten Kediri - Muhammad Junaidi Wahyu Anggra; Bayu Kresna Aji; Erfan Nawawi; Kholyfatusy Sya’idah; Putri Azalia Nur Rochmayanti; Ertika Fitri Lisnanti (Universitas Islam Kadiri, 2017)
The majority of Pagung villagers are livestock farmers, especially cows. However, the lack of livestock breeding causes the community to rearrange simply and result in a lack of environmental concern from livestock waste in the form of feces. Pemuda Pagung village majority of junior high school so difficult to find decent work and many are unemployed. The PKM-M team provides innovation to establish an entrepreneurial youth group with mix farming system with the aim of solving the economic, social and environmental problems of the community. Using the training assistance as much as 11 times for 3 months able to form a village youth group